3D Nanofabrication of SiOC Ceramic Structures. Issue 12 (23rd October 2018) - Brigo, Laura; Schmidt, Johanna Eva Maria; Gandin, Alessandro; Michieli, Niccolò; Colombo, Paolo; Brusatin, Giovanna
Abstract: Shaping ceramic materials at the nanoscale in 3D is a phenomenal engineering challenge, that can offer new opportunities in a number of industrial applications, including metamaterials, nano‐electromechanical systems, photonic crystals, and damage‐tolerant lightweight materials. 3D fabrication of sub‐micrometer ceramic structures can be performed by two‐photon laser writing of a preceramic polymer. However, polymer conversion to a fully ceramic material has proven so far unfeasible, due to lack of suitable precursors, printing complexity, and high shrinkage during ceramic conversion. Here, it is shown that this goal can be achieved through an appropriate engineering of both the material and the printing process, enabling the fabrication of preceramic 3D shapes and their transformation into dense and crack‐free SiOC ceramic components with highly complex, 3D sub‐micrometer architectures. This method allows for the manufacturing of components with any 3D specific geometry with fine details down to 450 nm, rapidly printing structures up to 100 µm in height that can be converted into ceramic objects possessing sub‐micrometer features, offering unprecedented opportunities in different application fields. Abstract : Here, 3D nanofabrication of a preceramic polymer by 2 Photon laser lithography and conversion to a fully ceramized, dense and crack‐free SiOC ceramic component are demonstrated. An appropriate engineering of both the material and the printing process allows the rapid manufacturing of any 3D specific geometry up to 100 µm in height with sub‐micrometer architecture.